Atitudes implícitas de estereótipos de gênero de mulheres praticantes de rúgbi - Tardeli, Lara de Azevedo (2023)
Based on a feminist perspective of Behavior Analysis and on the assumption that sport is na enable of empowerment, this study aimed to investigate whether the practice of rugby by women, being a sport culturally practiced by men, contributes to the reduction of gender bias - compared to practitioners of other sports and non-practitioners of sports - using a measure of implicit attitudes of gender stereotypes. Thirty women participated in the research, divided in three groups: the experimental group, composed by ten women rugby players, and two control groups: one composed by ten women not practicing sports and the other by tem women practicing sports in which female participation is historically considered more accepted. A Sociodemographic Questionnaire was applied, the Athletic Identity Measurement Scale (AIMS) to investigate Athletic Identity, and the Function Acquisition Speed Test (FAST) to access implicit attitudes of gender stereotypes. The results of the FAST were analyzed by comparing the FAST Effect between groups of participants (experimental and control groups). No significant differences were found in the comparison between groups regarding gender bias. The results are discussed and future investigations suggested.